Regulatory Functions of the N-terminal Domain of the 70-kDa Subunit of Replication Protein A (RPA) - Binz, Sara K. (American Society for Biochemistry and Molecular Biology, 2008)
Replication protein A (RPA) is the major single-stranded DNA-binding protein in eukaryotes. RPA is composed of three subunits of 70, 32, and 14 kDa. The N-terminal domain of the 70-kDa subunit (RPA70) has weak DNA binding activity, interacts with proteins, and is involved in cellular DNA damage response. To define the mechanism by which this domain regulates RPA function, we analyzed the function of RPA forms containing a deletion of the N terminus of RPA70 and mutations in the phosphorylation domain of RPA (N-terminal 40 amino acids of the 32-kDa subunit). Although each individual mutation has only modest effects on RPA activity, a form combining both phosphorylation mimetic mutations and a deletion of the N-terminal domain of RPA70 was found to have dramatically altered activity. This combined mutant was defective in binding to short single-stranded DNA oligonucleotides and had altered interactions with proteins that bind to the DNA-binding core of RPA70. These results indicate that in the absence of the N-terminal domain of RPA70, a negatively charged phosphorylation domain disrupts the activity of the core DNA-binding domain of RPA. We conclude that the N-terminal domain of RPA70 functions by interacting with the phosphorylation domain of the 32-kDa subunit and blocking undesirable interactions with the core DNA-binding domain of RPA. These studies indicate that RPA conformation is important for regulating RPA-DNA and RPA-protein interactions.